2014
DOI: 10.1099/mic.0.079020-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple personalities of the RNA polymerase active centre

Abstract: Transcription in all living organisms is accomplished by highly conserved multi-subunit RNA polymerases (RNAPs). Our understanding of the functioning of the active centre of RNAPs has transformed recently with the finding that a conserved flexible domain near the active centre, the trigger loop (TL), participates directly in the catalysis of RNA synthesis and serves as a major determinant for fidelity of transcription. It also appears that the TL is involved in the unique ability of RNAPs to exchange catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
(48 reference statements)
0
11
1
Order By: Relevance
“…Altogether, these observations extend the concept of factor-dependent exchange of RNAP activities in response to various regulatory stimuli (16,21,34), and suggest that various secondary channel regulators may play a general role in metal homeostasis and, more broadly, in adaptation to complex ecological niches.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Altogether, these observations extend the concept of factor-dependent exchange of RNAP activities in response to various regulatory stimuli (16,21,34), and suggest that various secondary channel regulators may play a general role in metal homeostasis and, more broadly, in adaptation to complex ecological niches.…”
Section: Discussionmentioning
confidence: 60%
“…The TL in the RNAP active site has previously been implicated in functional interplay with Gre factors, which should replace it to stimulate the RNA cleavage reaction (16,29,34). To reveal whether the TL is important for pause stimulation by Gfh factors, we analyzed mutant Dra RNAP with a deletion in the TL (Fig.…”
Section: Gfh Factors Stimulate Transcriptional Pausing In the Presencmentioning
confidence: 99%
“…Nevertheless, competition experiments between GreB and DksA show that each protein's activity is unimpeded in the excess (10-to 300-fold) presence of the other protein, raising the possibility that the proteins are recruited to distinct subpopulations of ECs (18,20). In contrast, other observations have been taken to suggest that multiple SC factors can bind simultaneously to RNAP; such simultaneous binding is inconsistent with simple binding competition (19,20,22).…”
mentioning
confidence: 99%
“…In particular, a combination of crystallographic data and structural modeling suggests that when GreB binds in the SC, it is likely to insert into the RNAP active site in a manner that inhibits nucleotide addition to the nascent transcript (13,(17)(18)(19)(20). However, functional studies have not demonstrated inhibition by wild-type Gre proteins in vitro (17,20), raising the question of how the proteins can stimulate transcript cleavage but not interfere with transcript elongation.…”
mentioning
confidence: 99%
See 1 more Smart Citation